Warming up through buildings and roads: what we know and should know about the urban heat island effect on bees - Polidori, Carlo; Ferrari, Andrea; Ronchetti, Federico; Tommasi, Nicola; Nalini, Elia (Frontiers in Bee Science, 2023)
Urbanization leads to cities having higher temperatures than surrounding non-urban areas [this is known as the urban heat island (UHI) effect]. Very little is known about the impacts of the UHI effect on bees, despite the importance of temperature on many aspects of bees’ life suggesting that these may be not negligible. In this study, we aimed to highlight how the UHI effect could impact relevant functional traits of bees in cities, proposing several ad hoc hypotheses for traits that have thus far been investigated only in few studies or not at all, based on what we know from non-urban studies. The UHI effect was shown to influence bee body size, and generally tended to reduce the body size of bees in cities. Urban temperature may also affect bees’ wing morphology, and thus their overall flight morphology parameters. Individuals may be more brightly colored in cities. Bee ommatidial size and the number of antennal thermoreceptors they have may be smaller and fewer, respectively, in cities than in non-urban areas. As expected, because urban bees face a higher risk of desiccation, higher proportions of alkanes and longer main-carbon chain lengths are expected in their cuticular hydrocarbon (CHC) profiles. Stress biomarkers can also occur at greater concentrations in bees in cities and specific bacteria in the bee gut may occur at lower abundances. Warm urban temperatures may impact the life cycle of pathogens by reducing their proliferation. Aggression levels may be increased, and eusocial species may present more worker phases per year due to the UHI effect. All of these proposed impacts could be likely more visible in solitary and primitively eusocial bee species, which are those suspected to have a more limited dispersal ability. Comparative studies would help in the proper testing of these hypotheses.